A widely expressed βIII spectrin associated with Golgi and cytoplasmic vesicles - Stankewich, Michael C. (The National Academy of Sciences, 1998)
Spectrin is an important structural component of the plasma membrane skeleton. Heretofore-unidentified isoforms of spectrin also associate with Golgi and other organelles. We have discovered another member of the β-spectrin gene family by homology searches of the GenBank databases and by 5′ rapid amplification of cDNA ends of human brain cDNAs. Collectively, 7,938 nucleotides of contiguous clones are predicted to encode a 271,294-Da protein, called βIII spectrin, with conserved actin-, protein 4.1-, and ankyrin-binding domains, membrane association domains 1 and 2, a spectrin dimer self-association site, and a pleckstrin-homology domain. βIII spectrin transcripts are concentrated in the brain and present in the kidneys, liver, and testes and the prostate, pituitary, adrenal, and salivary glands. All of the tested tissues contain major 9.0-kb and minor 11.3-kb transcripts. The human βIII spectrin gene (SPTBN2) maps to chromosome 11q13 and the mouse gene (Spnb3) maps to a syntenic region close to the centromere on chromosome 19. Indirect immunofluorescence studies of cultured cells using antisera specific to human βIII spectrin reveal a Golgi-associated and punctate cytoplasmic vesicle-like distribution, suggesting that βIII spectrin associates with intracellular organelles. This distribution overlaps that of several Golgi and vesicle markers, including mannosidase II, p58, trans-Golgi network (TGN)38, and β-COP and is distinct from the endoplasmic reticulum markers calnexin and Bip. Liver Golgi membranes and other vesicular compartment markers cosediment in vitro with βIII spectrin. βIII spectrin thus constitutes a major component of the Golgi and vesicular membrane skeletons.